Study of Moisture Absorption Behaviour of Agave Americana Fibre Reinforced Composite Material - Ishita (My University, 2018)
Due to the increase in concern for the environment, the material scientists are shifting towards the natural fibres. Composites based on Agave Americana fibre reinforced epoxy resin are prepared using hand lay-up method. Agave Americana fibres are chemically treated with 2%(w/v) NaOH, alkali hornification and water hornification to reduce their affinity for water. Four cycles were carried for the water and alkali hornification. The SEM studies were carried out to analyze the cross section of the untreated fibre, NaOH treated fibre, alkali hornified fibre and water hornified fibres, the decrease in the holes and smoothing of texture is observed after the treatment was observed. The specimens prepared by ASTM D570-98 were characterized in terms of water absorption properties under controlled humidity and temperature environments. The effects of the treatment were investigated by means of a digital weighing machine and further validated with FEM analysis in the Abaqus software. The test partly attributed to disappearance of hydrophilic nature of the fibre. The alkali hornification gave the best results. The mass gain of the NaOH treated and the alkali hornified specimen are close in some conditions. The maximum mass gain is 8.02% at 75° C (Water Bath) in the untreated fibres whereas after the alkali hornification, NaOH treatment and water hornification the mass gain is 4.72%, 5.08% and 6%, respectively.
Keywords: Natural fibre; Agave Americana fibre; Moisture absorption; Chemical modifications; Mass gain analysis; FEA; Experimentation